Digital-palmar dermatoglyphics characteristics of patients living with schizophrenia in Ghana - Niena Samira Majeed; Benjamin Arko-Boham; Delali Kudzo Fiagbe; Kevin Kofi Adutwum-Ofosu; Nii Koney-Kwaku Koney; Bismarck Afedo Hottor; Richard Michael Blay; Mubarak Abdul-Rahman; John Ahenkorah (All Life, 2023)
The World Health Organization has acknowledged the gap in schizophrenia diagnoses and recommended further research to identify tools and biomarkers for the disease’s early detection. Because the skin and brain have a common ectodermal origin, dermatoglyphics are hypothesized to serve as a potential mirror for the identification of risks and characteristics of neuropsychiatric diseases. This study aimed to determine the digito-palmar dermatoglyphic patterns of schizophrenia patients in Ghana. Digito-palmar dermatoglyphics were obtained using a digital scanner, and the details studied. Individuals living with schizophrenia in Ghana were significantly characterized by low odds of vestige pattern in the hypothenar region, low odds of palmar creases 300, and high and low odds of radial loop (RL) and plain arch (PA) respectively at the finger patterns relative to the control group [OR (95% CI): vestige, 0.2 (0.06–0.69), P = 0.01; palmar creases 300, 0.1 (0.01–0.99), P = 0.049; PA, 0.4 (0.3–0.7), P < 0.001; RL, 1.9 (1.0–3.7), P = 0.044]. Individuals with schizophrenia were also characterized by low mean left-hand a-b ridge count and mean right hand atd angle compared to controls. These differences could be explored as a potential biomarker in diagnosing and early detection of schizophrenia in Ghanaians.